The transformation of hospital medicine to tackle the COVID-19 pandemic crisis - Nirvani Goolsarran; Veena Lingam; Sadia Abbasi (Greater Baltimore Medical Center, 2020)
The coronavirus disease 2019 (COVID-19) pandemic is placing extraordinary strains not only on hospital-wide systems but most especially on hospital medicine across the nation. The specific challenges faced by our hospitalist services are unfathomable. Hospitalist leaders are tasked to rapidly restructure clinical operations to accommodate the large surge in COVID-19 patients.Â In this perspective, we focus on the management strategies conducted by the Division of Hospital Medicine to tackle the major crisis that specifically impacted the general medicine services.